Основи конституційного ладу в системі конституції України - Прієшкіна, О.В. (Часопис Київського університету права, 2010)
У статті аналізуються основні засади конституційного ладу в Конституції України. Досліджуються проблеми та перспективи розвитку основ конституційного ладу та основні їх риси. Ключові слова: Конституція України, конституційний лад, основи конституційного ладу. В статье анализируются основные черты конституционного строя Украины в Конституции Украины. Исследуются проблемы и перспективы развития основ конституционного строя и основные их черты. Ключевые слова: Конституция Украины, конституционный строй, основы конституционного строя. In this article the main traits of the constitutional system of Ukraine in the Constitution of Ukraine are analyzed. The problems and prospects of the development of the constitutional system are researched and their main traits are analyzed. Key words: Constitution of Ukraine, constitutional system, the bases of constitutional system.